Bipolar and psychotic disorders in elite athletes: a narrative review. Issue 12 (16th May 2019) - Currie, Alan; Gorczynski, Paul; Rice, Simon M; Purcell, Rosemary; McAllister-Williams, R Hamish; Hitchcock, Mary E; Hainline, Brian; Reardon, Claudia L
Abstract : Bipolar and psychotic disorders are relatively common and likely to have a significant impact on quality of life and functioning which, in the context of elite sport, includes a potential negative impact on sporting performance. For this narrative review article, the literature on bipolar and psychotic disorders in elite athletes was comprehensively searched, and little empirical research was found. A diagnosis of bipolar or psychotic disorders may be challenging in elite athletes because of complicating factors related to the modifying role of exercise and potential precipitating impact of substance use. Medications used to treat bipolar and psychotic disorders may have side effects particularly problematic for elite athletes. Future research should be tailored to the specific characteristics and needs of elite athletes and to the sporting context in which the disorders may arise. Specifically, further research is needed on the prevalence and incidence of these conditions in elite athletes and the impact of both the disorders and their treatments on sporting performance.